INFORMATION AND COMMUNICATIONS TECHNOLOGIES – THE WAY OF SOCIALIZATION OF PEOPLE WITH PROFOUND VISUAL IMPAIRMENTS - Serhii I. Netosov (Інформаційні технології і засоби навчання, 2015)
The article analyzes the software and hardware, that give people with profound visual impairments the opportunity to work on the computer. Attention is drawn to the Braille printers, relief-dot displays, voice synthesizers, scanners that can read, adaptation and correction programs and so on. It is emphasized that ICT for the blind is a factor of their inclusion in the life as the subjects of action. For solving this problem people with profound visual impairments need systemic help of the state and civil society in getting programs and equipment, because they are high-tech, and therefore expensive. It is important to spread the information about the activity of the centers of tiflo-computerization, to organize the laboratories of correction and socialization of people with profound visual impairments, to provide the training of the specialists.